2015
DOI: 10.1021/acs.langmuir.5b03470
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Responsive Release Controlled by Hot Spot Effect

Abstract: Magnetically triggered drug delivery nanodevices have attracted great attention in nanomedicine, as they can feature as smart carriers releasing their payload at clinician's will. The key principle of these devices is based on the properties of magnetic cores to generate thermal energy in the presence of an alternating magnetic field. Then, the temperature increase triggers the drug release. Despite this potential, the rapid heat dissipation in living tissues is a serious hindrance for their clinical applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 32 publications
7
74
0
2
Order By: Relevance
“…This "hot spot" or "local magnetic hyperthermia" effect has already been observed for other DDS based on polymers (e.g. MNPs coated with polymers13,18 ; MIP-…”
supporting
confidence: 62%
See 1 more Smart Citation
“…This "hot spot" or "local magnetic hyperthermia" effect has already been observed for other DDS based on polymers (e.g. MNPs coated with polymers13,18 ; MIP-…”
supporting
confidence: 62%
“…Recently, some research groups have demonstrated that polymeric-MNPs nanocarriers (Magnetic Molecularly Imprinted Polymer Nanoparticles 16 , polymer coated MNPs [17][18][19] ) can release their payload without macroscopic heating (athermal conditions). In this case, MNPs act as individual "hot spots" and generate a localized heating, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one study by Rühle et al, it was reported that the temperature 20 nm from the SPION surface could be as high as 65 C, under conditions where there is no increase in the global temperature of the sample (Rühle, Datz, Argyo, Bein, & Zink, 2016). Others have reported similar findings, with temperatures reaching >43 C and triggering drug release at distance~20 nm from the SPION surface (Guisasola et al, 2015). However, some studies have reported more modest findings, with temperatures reaching only 45 C within 0.5 nm of the SPION surface and dropping off exponentially with distance (Riedinger et al, 2013).…”
Section: Magnetically Induced Drug Releasementioning
confidence: 86%
“…The resulting particles exhibit a discoid or lens shape depending on the chemical properties of the grafted layer. The interfacial behavior of polymer ligands can be tuned in situ by altering solvent properties, such as temperature and pH . Soft particles composed of polymer gels have also been observed to deform upon adsorption, where the extent of particle deformation at the interface is governed by a competition between particle elasticity and surface tension .…”
Section: Assembly Dynamics and In Situ Characterization Of Nanomatementioning
confidence: 99%